Temperature-Dependent Oxygen Isotope Fractionation in Plant Cellulose Biosynthesis Revealed by a Global Dataset of Peat Mosses - Xia, Zhengyu; Yu, Zicheng (Frontiers in Earth Science, 2020)
The oxygen isotope composition (δ18O) of plant cellulose has been widely used to study ecohydrological processes of ecosystems as well as to reconstruct past climate conditions in terrestrial climate archives. These applications are grounded on a key assumption that the biochemical fractionation during cellulose synthesis is a constant around +27‰ and is not affected by environmental factors. Here we revisit the influence of temperature on biochemical fractionation factor during cellulose synthesis using a global compilation of Sphagnum cellulose δ18O data. Sphagnum (peat mosses) are known for inhabiting waterlogged peatlands and possessing unique physiological strategy in that their cellulose δ18O could closely reflect growing-season precipitation δ18O. Although within-site cellulose δ18O variability shows a median standard deviation of 0.7–0.8‰ resulting from different degree of evaporative enrichment of 18O in metabolic leaf water, this evaporative enrichment is a small quantity due to the external capillary “water buffer” in Sphagnum mosses. Using site-specific minimum cellulose δ18O data that most likely reflect the signal of unevaporated source water, we show that the apparent enrichment factor between cellulose and precipitation δ18O increases with decreasing air temperature. In particular, the apparent enrichment factor could reach as high as 32‰ when growth temperature is below 5 °C. This observational dataset extends the support for the temperature-dependent oxygen isotope fractionation in plant cellulose synthesis previously demonstrated in laboratory experiment, with implications for paleoclimate and plant physiology studies that employ cellulose δ18O measurements particularly in alpine regions.